P Penerapan algoritma equivalence class transformation (eclat) dalam pencarian adverse event obat simvastatin - Ali, Ali Husin Siregar; Alwis, Alwis Nazir; Iis, Iis Afrianty; Elvia, Elvia Budianita; Fitri, Fitri Insani (Universitas Muhammadiyah Riau, 2023)
Cholesterol is a type of fat that circulates in the bloodstream and has an important role in body functions. However, excess cholesterol levels can cause various problems in the body that interfere with the heart, blood vessels, and brain systems. Simvastatin is a lipid-lowering drug in the blood that can reduce cholesterol. In this study, an adverse event was conducted which is an unwanted event in the world of health in the consumption of simvastatin drugs using the Equivalence Class Transformation (ECLAT) algorithm. The data used came from the Food and Drug Administration (FDA) which amounted to 22560 data. Data is managed by the Knowledge Discovery in Databases (KDD) process which goes through several stages, namely data selection, data processing, data transformation, and data mining. Test results are measured based on the lift ratio value which aims to measure the validity of the resulting rule. The test was conducted using a minimum support value of 0.001 and obtained the best lift ratio value of 886.00. In the combination of 2 items, the best rule is